PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN EKOWISATA AIR TERJUN GURUH GEMURAI DESA KASANG KECAMATAN KUANTAN MUDIK KABUPATEN KUATAN SINGINGI - Metri, Erwis; Oktorini, Yossi; M. Mardhiansyah, M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Guruh Gemurai Waterfall is one ofthe ecotourism object in Kuantan Singingi Regency, especially in Kuantan Mudik Subdistrict. This research aims to determine the public perception of ecotourism development of Guruh Gemurai Waterfall in Kasang Village, Kuantan Mudik Subdistrict, Kuantan Singingi Regency. This research was conducted directly in the field with data collection methods through questionnaires and interviews to the people of Kasang Village, Kuantan Mudik Subdistrict. Methods of taking respondents using Slovin formula with incidental techniques. Data collection in this research also uses observation and documentation in the field. The data obtained is then reduced to a summary presented in the form of brief descriptions, tables and graphs. Data analysis was done by qualitative, quantitative approach with percentage and Likert Scale. The development of ecotourism GuruhGemurai Waterfall in perception well with the percentage of communityanswers 84.04%.All elements of society in Kasang Village want more involved in the management and development of ecotourism GuruhGemurai waterfall. Key words: Community Perception, Development, Ecotourism, Guruh Gemurai Waterfall.